2021
DOI: 10.1038/s41598-021-99137-8
|View full text |Cite|
|
Sign up to set email alerts
|

Spatio-temporal patterns of childhood pneumonia in Bhutan: a Bayesian analysis

Abstract: Pneumonia is one of the top 10 diseases by morbidity in Bhutan. This study aimed to investigate the spatial and temporal trends and risk factors of childhood pneumonia in Bhutan. A multivariable Zero-inflated Poisson regression model using a Bayesian Markov chain Monte Carlo simulation was undertaken to quantify associations of age, sex, altitude, rainfall, maximum temperature and relative humidity with monthly pneumonia incidence and to identify the underlying spatial structure of the data. Overall childhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Many studies in the past have also reported a high number of common cold cases 48 , 49 and other diseases 50 52 during the monsoon season which was also noted in this study. During rainy seasons, it is plausible that many people are restricted to homes where they gather together, during which time infections can spread quickly.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Many studies in the past have also reported a high number of common cold cases 48 , 49 and other diseases 50 52 during the monsoon season which was also noted in this study. During rainy seasons, it is plausible that many people are restricted to homes where they gather together, during which time infections can spread quickly.…”
Section: Discussionsupporting
confidence: 87%
“…Another possible reason for an increase in cases following rainfall might be due to contamination of surface water, which is the predominant source of drinking water in the country. Contaminated water and poor sanitation have been associated with high rates of respiratory infections 52 , 53 . An increase in cases of respiratory infections in the aftermath of monsoon flooding has been quite common 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, air pollution in southern Bhutan, where Samtse is located, is expected to be higher with increased risk [32][33][34][35]. An earlier study showed that pneumonia was significantly higher in some parts of the southern sub-districts in Bhutan [19]. Lastly, the surface water from streams is the main source of drinking water in rural Bhutan [36].…”
Section: Discussionmentioning
confidence: 99%
“…In the southern districts of Bhutan, increasing incidence of dengue and scrub typhus are responsible for increasing hospital visits and admissions [14][15][16][17]. Other reported causes of fever admissions include typhoid, chikungunya and respiratory illness [18,19], while the incidence of malaria has been on the decline in recent years [16,20]. In Bhutan's efforts to provide free and quality healthcare to all, there is a need for a better understanding of the epidemiological characteristics and aetiologies of fever and the length of hospital stay among the population living in the sub-tropical region in Bhutan.…”
Section: Introductionmentioning
confidence: 99%